Cultural management in the National Palace of Mexico: use and heritage conservation - Rivero, Lilia (Ge-conservacion, 2017)
Conservation of Mexico National Palace is a complex labor, since implies the preservation, not only of the material aspects of the building and the objects contained within, but also all the immaterial values reflected on the walls of the structure that mirrors the historic continuity of Mexico and therefore part of the national identity. Due these conditions, National Palace is in our days the most emblematic and symbolical government building of the country. In order to preserve the monument, a comprehensive conservation-cultural management program has been developed and implemented, considering operational aspects of the monument management, that is also part of the cultural infrastructure of Mexico City, since this historical complex attracts around 340 000 visitors each year. In addition, among the Conservator´s Office strategy has been to promote collaboration between different actors involved with the use, operation and conservation of the monument, in which are included external governmental offices and academic institutions, both national and international. This collaborative approach has been crucial in order to implement the Management Program for the conservation of the monument.